DIFFERENCES IN SOFT TISSUE THICKNESS OF THE CHIN BASED ON MANDIBLE GROWTH PATTERN IN ADULT PATIENTS: PERBEDAAN KETEBALAN JARINGAN LUNAK DAGU BERDASARKAN POLA PERTUMBUHAN MANDIBULA PASIEN DEWASA - Sofyanti, Ervina; Regoo, Vinoshinie (Dentika: Dental Journal, 2016)
The facial appearance is as important as the occlusal relationship in any dental treatment. The chin that represents the largest segment of the lower third facial proportion for both sexes is overlooked when it comes to the aesthetic alteration of the face. Proper understanding about anatomical changes and chin artless movements, or in conjunction with formal orthognathic surgery, is paramount. The purpose of this study was to evaluate the difference of soft tissue chin (STC) thickness which was measured from skeletal Pogonion (Pog) to soft tissue pogonion (Pog’) in various mandibular patterns. The cephalograms lateral pretreatment of adult patients (â‰¥21 years) that divided into three groups (hypo divergent, average, hyper divergent) were analyzed with one-Way Anova. Soft tissue chin (STC) thickness which was measured from skeletal Pogonion (Pog) to soft tissue pogonion (Pog’). Various mandibular pattern are based on mandibular plane inclination (MP) to anterior cranial base (SN) as normal value between 27°-37°. There were significant differences of soft tissue chin thickness in various mandibular pattern. Mandibular pattern might camouflage lower third of the face from soft tissue profile, especially pogonion as the most anterior point on the contour of the chin. The average of normal soft tissue chin thickness which 11.68±2.0mm (according to Holdaway) can be served as guidelines to predict the appearance of the chin, so that the multidisciplinary treatment approach, like genioplasty can be informed from the beginning in camouflage orthodontics treatment.